Scrutinising the Most Efficient Explant for Agrobacterium Mediated Transformation in Indian Cassava Variety, H226 - Jayaseelan, Dhanya; Deepthi, DC; Beena, MR; Sheela, MN; Makeshkumar, T (JOURNAL OF ROOT CROPS, 2017)
The most reliable and competent explant for producing transgenic lines were identified in farmer preferred Indian cassava variety, H226, utilizing four different tissue types viz., apical meristem (AM) young cotyledon (YC), compact embryogenic structures (CES) and friable embryogenic callus (FEC) through transformation with Agrobacterium tumefaciens strain, AGL0 harbouring the plant transformation vector pOYE153 having uidA gene conferring GUS activity and Npt II marker (AGL0/ pOYE153). The transgenic lines were confirmed for the presence and expression of transferred selectable marker gene Npt II as well as visual marker gene GUS by molecular analysis (PCR and Nucleic Acid Spot Hybridisation (NASH)) and GUS histochemical assay. This study reported maximum frequency of GUS gene expression (64%) in cotyledon explants, producing six putative transgenic lines and it was followed by CES explants, producing two lines in selection medium. Although FEC GUS assay proved positive for 43% of the tested samples, only one transgenic line was regenerated and the recovery was quite difficult. In the present study, young cotyledon was identified as the most suitable target tissue for Agrobacterium mediated genetic transformation of cassava variety, H226.